Feeding Dynamics and Interspecific Interactions of Vulture at a Supplementary Feeding Site in Tanahun District, Nepal (Journal of Forest and Natural Resource Management, 2025)
Vulture populations in South Asia have declined sharply due to veterinary diclofenac, leaving four of Nepal’s nine species listed as Critically Endangered. In response, Nepal has promoted conservation interventions through Vulture Safe Zones and supplementary feeding sites. This study examined species composition, feeding dynamics, and interspecific interactions at a community-managed site in Gachhepani, Tanahun District, from February to May 2024. Six carcasses on separate days were observed using total counts and scan sampling at 10-minute intervals over 30 minutes. Social interactions, including attacks, chases, displacements, and snatches, were documented. Six vulture species were recorded, with Himalayan vultures (Gyps himalayensis) being most abundant (50%), followed by White-rumped vultures (Gyps bengalensis) (30%). A total of 239 attacks, 67 chases, 68 displacements, and 47 snatches were observed, mainly involving Himalayan vultures, indicating dominance due to large size and aggression. Carcass mass strongly correlated with consumption time (p